Previous Mode of Education and Future Learning Style Preferences among Medical students: A Cross-Sectional Study - Saleem, Aqsa; Fatima, Sampana; Saleem, Abdullah; Saleem, Iqra (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To find the association of different learning styles with gender and previous mode of education among 1st and 2nd year medical students at a private medical college in Lahore, Pakistan. Method A cross-sectional study was conducted on 1st and 2nd year MBBS students of Shalamar Medical & Dental College. Data was collected using a validated questionnaire comprising 44 questions in four domains, active/reflective, visual/verbal, sequential/global, and sensitive/intuitive. Results The total number of participating students was 297, 132 were male and 165 were female. We found that students mostly preferred the active learning style over reflective and sequential over global, sensitive over intuitive, and visual over verbal. We also found that the previous mode of education was significantly associated with active/reflective and sensitive/intuitive. Conclusion Most of the students preferred visual overactive, sensitive, and sequential learning styles. The previous mode of education strongly impacts the preference for learning styles in professional academic careers. By adapting the previous mode of education of the majority of students in future institutions, the outcomes of academic scores and conceptual learning can be improved, which is vital to make a good doctor.